Model Pengelolaan Bantuan Sosial dalam Menanggulangi Kemiskinan di Kota Tanjungbalai Berbasis SATF Values dengan Pendekatan Maqashid Syariah - Dedeng Irawan; Roni Parlindungan Sipahutar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The urgency of this research is based on the impact of the problem of inequality in social welfare, which has led to the problem of prolonged poverty. To determine the extent of a poverty alleviation program that has been implemented, the government should be able to evaluate the models of social assistance management in alleviating poverty. In this study, the focus is on poverty alleviation efforts by applying the characteristics of the Prophet Muhammad when receiving social assistance from the government, namely telling the truth (shiddiq), being trustworthy (amanah), having intelligence (fathonah), and being transparent (tabligh), which the researcher tries to link with the five indicators of maqashid sharia which are the focus of discussion in this study. The purpose of this study is to determine how the management model for managing social assistance in an effort to alleviate poverty. In addition, this study also explores the SATF Values ​​​​mediating the relationship between social assistance management in alleviating poverty, as well as how the role of maqashid sharia in mediating the relationship between social assistance management in alleviating poverty. The research method uses a quantitative approach. The population in this study was all recipients of the Family Hope Program in Tanjungbalai City in 2024. The sampling technique used accidental sampling, where researchers selected individuals who were available and deemed suitable as data sources. The sample selection was conducted using the Slovin formula, resulting in a sample size of 400 recipient families in Tanjungbalai City. The data analysis technique used in this study was Partial Least Squares (PLS). The equation model in Partial Least Squares is a Structural Equation Modeling (SEM) equation, implementing an approach based on Variance or Component-based structural equation modeling.